Use of ATP bioluminescence to survey the contamination of dental goggles in surgical removal of impacted mandibular third molars - Kaoru Murakami; Chikashi Minemura; Koji Yamamura; Tomohiro Takayama; Yasushi Kimura; Hidetaka Yokoe (Elsevier, 2021)
The importance of protecting the eyes from infectious agents in patients' blood and saliva during dental surgery has long been known, but the global COVID-19 pandemic has made this even more important. The use of ATP bioluminescence to investigate the contamination of dental goggles during the surgical removal of impacted teeth in the present study indicates their importance for protecting the eyes from aerosols from the front, from above, and from the sides.